2016
DOI: 10.1080/02688697.2016.1229749
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of surgery for adult hydrocephalus patients in Sweden

Abstract: Incidence of hydrocephalus surgery increased significantly during 2004-2011, specifically in elderly patients. Surgical treatment of iNPH markedly improved functional independence, but the improvement rate was low compared to recent single- and multicentre studies. Thus, the potential for surgical improvement is likely lower than generally reported when treating patients as part of everyday clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
4
42
4
Order By: Relevance
“…Another explanation for our lower improvement rate was that our inclusion was consecutive and encompassed elderly patients and patients with severe comorbidity who would have been excluded in many prospective studies with strict inclusion criteria. 5 The length of follow-up in the present study was 12 months, which is in line with the majority of previous studies reporting outcome. 4 In contrast to our results, Thompson et al reported that 83% of their patients over 80 years improved.…”
Section: Clinical Outcome Of Shunt Surgerysupporting
confidence: 90%
See 3 more Smart Citations
“…Another explanation for our lower improvement rate was that our inclusion was consecutive and encompassed elderly patients and patients with severe comorbidity who would have been excluded in many prospective studies with strict inclusion criteria. 5 The length of follow-up in the present study was 12 months, which is in line with the majority of previous studies reporting outcome. 4 In contrast to our results, Thompson et al reported that 83% of their patients over 80 years improved.…”
Section: Clinical Outcome Of Shunt Surgerysupporting
confidence: 90%
“…6 However, our improvement rate is in line with a large registry study from Sweden using a similar method for clinical evaluation, with 58% improvement. 5 The length of follow-up in the present study was 12 months, which is in line with the majority of previous studies reporting outcome. 4 Studies with follow-up time longer than three years report slightly lower improvement rates than studies with short follow-up.…”
Section: Clinical Outcome Of Shunt Surgerysupporting
confidence: 90%
See 2 more Smart Citations
“…Shunt surgery is a common treatment for iNPH, and the incidence of surgery has increased over the last decade. 17 In Sweden, adjustable shunt valves have been used to a varying extent since the beginning of the 1990s, 20 and when fixed valves are still applied, it is often for shortterm economic reasons. Considering that SDHs were as common in patients having fixed as well as adjustable shunts, health economics investigations might well prove adjustable shunts to be a less expensive option despite their higher purchase price.…”
Section: Treatment Of Sdhmentioning
confidence: 99%